Bullous eruption of SLE--a case report and investigation of the relationship of anti-basement-membrane-zone antibodies to blistering. - Burge, S; Schomberg, K; Wojnarowska, F (1991)
We describe the clinical and immunopathological findings in a patient with a bullous eruption and systemic lupus erythematosus (SLE). The bullous eruption preceded a dramatic flare of the SLE with a rise in anticardiolipin antibodies and life-threatening cardiac vasculitis. The clinical and histological findings were similar to those described in the classic bullous eruption of SLE but, unlike previous cases, IgG anti-basement-membrane-zone (anti-BMZ) antibodies were detected on the epidermal as well as the dermal side of the split in chemically separated human skin. We screened the sera of another eight patients with SLE and 10 patients with chronic cutaneous lupus erythematosus (CCLE) without evidence of systemic involvement for the presence of anti-BMZ antibodies and demonstrated that these were present in a low titre in a further two SLE patients neither of whom had a history of blistering. Once more there was binding to both sides of the split. We conclude that although there may be low titres of antibodies to several BMZ antigens in patients with SLE, these are not always associated with blistering and their role in the initiation or perpetuation of cutaneous disease is uncertain.